Development of houseplant automated watering system based on moisture and temperature humidity condition: article / Ahmad Husayni Mohd Taher - Mohd Taher, Ahmad Husayni (2019)
In this paper, the project is set up to find a visible and cost erfective way of minimizing the use of water consumption. Impending scarcity wastage of this renewable resources, has led people to consider the use develop a system to preserve this natural resources, I sing the controlled motor pump to watering the plant it is one of the ways to implement water management. Controlled motor pump is based on the input data from the soil sensor and temperature humidity sensor. This project therefore involves the design and implementation microcon-controller using Atmega 328 V based on Adurino IJ no. The soil moisture sensor used to collect the analog leading of the soil moisture to ensure the soil is in moist condition whereas the temperature humidity sensor will record the reading of surrounding. All the reading will display on LCD as the information to user. The prototype's operation is achieved by connecting sensor to a microcontroller such that the motor pump will wait for input signal from the microcontroller. The programmed microcontroller hence delivers motor pump signal in pei'iodical time intervals for the motor to pump water to the soil.